The Building Public Trust Against to Law Enforcers in the Covid 19 Pandemic - Aghia Khumaesi Suud (International Journal of Research in Community Services, 2022)
The COVID-19 pandemic has had an impact on the credibility of the performance of law enforcement. National survey data and reports from various national media found a decline in public trust in law enforcement. With a normative juridical approach and using secondary data, this paper discusses what factors can restore public trust in law enforcement. First, the independence of law enforcement officers to improve the mentality of law enforcement in acting, secondly, it is necessary to develop a transformational bureaucratic leadership model to make changes in the field of services law enforcement in order to increase public trust.